Fully Guided Synthetic Osteochondral Resurfacing of a Large Stifle OCD Lesion Using a Patient-Specific Implant and Drill Guides - Moser, Jasmine; Haimel, Georg; Barker-Benfield, Karen; Leschnik, Katharina; Böttcher, Peter (VCOT Open, 2023)
Synthetic anatomical reconstruction of extensive, oval osteochondrosis dissecans (OCD) defects remains a challenge due to the ‘one shape fits all’ design of commercial round implants. This is further complicated by the inherent inaccuracy of free-hand implant positioning procedures. A 6-month-old German Shepherd presented with a 15 × 7.8 × 4.3 mm OCD defect at the lateral femoral condyle. A synthetic patient-specific implant (PSI) was designed, using the contralateral unaffected condyle as a template. Reaming of the implant bed was fully guided using a set of three-dimensional-printed drill guides. The implant, consisting of a titanium base and a polycarbonate urethane bearing surface, was press-fit into place. Temporary meniscal release of the cranial meniscal horn was repaired, followed by routine closure and postoperative care. The combination of PSI and matching drill guides resulted in an accurate restoration of the normal joint surface at the former defect area. At 6-week and 18-month follow-ups, mild joint effusion, unexpected soft tissue mineralization and a small joint mouse were present. No other complications were encountered, and the dog was clinically lameness-free. At 6 weeks and 6 months, computerized gait analysis documented increased loading of the affected limb from 36% preoperatively to 42 and 40%, on follow-up, respectively. Body weight distribution between both hindlimbs was nearly equal at the 6-month control with 1% difference in loading. Osteochondral resurfacing using a PSI appears to be a promising treatment option for large stifle OCD lesions in which other treatment modalities may not be eligible.
Keywords: OCD; stifle; resurfacing; patient-specific